Scientific-analytical components of assessment and selection of alternative options for implementing a development project in the pre-investment and preparatory phase of the cycle - Shpakov, A.V.; Shcherban, B.M.; Tsymbalisty, Y.V.; Gergi, M.S.; Katsyuba, I.R. (Ways to Improve Construction Efficiency, 2023)
The topic of assessment and selection of alternative options for implementing development projects in the pre-investment and preparatory phase is key in modern construction management, since it is at this stage that strategically important decisions are made that determine the success of the project as a whole. The scientific-analytical approach to assessing alternative options for implementing a development project includes a comprehensive analysis of risks, opportunities, economic feasibility, engineering and technical aspects, as well as legal and regulatory requirements. The pre-investment and preparatory phase of the project covers a wide range of tasks, including determining the feasibility of the project, market analysis, financial modeling, estimating the cost of resources, as well as choosing technological and organizational solutions. This phase is critically important, since it is at this stage that the basis for further investment decisions is formed. The importance of scientific and analytical components lies in ensuring objectivity and accuracy in choosing the most effective alternatives for project development, which allows minimizing risks and increasing the likelihood of successful implementation. The main tools of scientific and analytical assessment are comparative analysis methods, SWOT analysis, economic and mathematical modeling, as well as risk assessment using appropriate mathematical and financial models. Comparative analysis allows you to determine the advantages and disadvantages of various project implementation options, taking into account factors such as construction duration, cost, resource availability, environmental impact and engineering conditions. SWOT analysis, in turn, allows you to identify the internal strengths and weaknesses of the project, as well as external opportunities and threats that may affect its implementation. Economic and mathematical modeling allows you to forecast financial flows, determine the level of profitability of the project and assess the sensitivity to changes in various economic parameters. Risk assessment is an integral part of the analysis process at the pre-investment and preparatory phase. In particular, financial, market, technical and regulatory risks that may affect the implementation of the project are analyzed. Effective risk management includes the development of scenarios and the identification of opportunities for their minimization. In general, scientific and analytical components at the pre-investment and preparatory phase of the development project cycle allow you to make an informed decision on choosing the best option for project implementation, taking into account all available factors and risks. This contributes to cost optimization, improved work organization and increased efficiency of the subsequent stage of development project implementation.